Progressing from “mistress’ lap-dog to freeman”: Commemorating the Slavery Experience in the Hispanic World via the Narrative of Juan Francisco Manzano - Tarnóc, András (FOCUS: Papers in English Literary and Cultural Studies, 2023)
The essay, I wish to compare Manzano’s account to selected examples of North American slave narratives, especially that of Frederick Douglass, while exploring such related issues as the question of authorship, the description of slavery both in the Caribbean and the American South, the role of women in the institution of slavery, and the potential applicability of black stereotypes maintained in North American culture.